Are profiles of self-regulated learning and intelligence mindsets related to students’ self-regulated learning and achievement? - Hertel, Silke; Reschke, Katharina; Karlen, Yves (Learning and instruction, 2024)
Background - Research emphasizes the relevance of mindsets for SRL and academic achievement. - Aims - This paper reports three studies that aim to detect profiles of mindsets about SRL and intelligence, examine their relationship with students’ SRL, study-related beliefs, and academic achievement, and replicate the findings across samples. - Sample - Participants were Ntotal = 633 university students, with NStudy1 = 254, NStudy2 = 187, and NStudy3 = 192. - Methods - LPAs were run to identify mindset profiles, and Mplus’ auxiliary (BCH) function was applied to examine mean differences across profiles. - Results - All three studies identified the mindset profiles “Entity-Theory”, “Balanced-Theory”, and “SRL-Theory”. The analyses revealed an SRL-Theory advantage regarding SRL, study-related beliefs, and academic achievement. - Conclusions - These are the first studies to explore mindset profiles based on mindsets about SRL and intelligence. The identified mindset-based meaning systems provide diagnostic information for teaching and tailored interventions and stimulate the advancement of SRL and mindset theories.